A Bibliometric Analysis of Earnings Management - Loso Judijanto; Dila Padila Nurhasanah; Ilham Akbar Bunyamin (Westscience Press, 2026)
Earnings management remains one of the most extensively investigated phenomena in accounting and corporate governance research, reflecting persistent scholarly concern over the reliability of financial reporting. This study conducts a bibliometric analysis to map the intellectual structure, research trends, influential publications, and collaboration patterns within earnings management scholarship indexed in the Scopus database. Data were analyzed using VOSviewer to perform keyword co-occurrence analysis, overlay and density visualization, citation analysis, co-authorship analysis, institutional collaboration mapping, and country-level distribution mapping. The results reveal three major thematic clusters: a methodological and demographic cluster associated with empirical research design, a financial-economic cluster centered on earnings, investment, and decision making, and a governance cluster dominated by earnings management, corporate governance, accruals, and agency theory. Citation analysis identifies foundational works on discretionary accrual measurement and real activities manipulation as the most influential contributions shaping the field. Co-authorship and institutional mapping reveal relatively fragmented research communities anchored by prolific scholars, while country-level analysis indicates pronounced dominance of United States-based institutions with limited international collaboration density. This study contributes a structured overview of earnings management research development and identifies research gaps concerning governance mechanisms, real activities manipulation, and cross-country institutional context for future scholarship.